Визначення силових факторів, що діють на підресорений корпус колісної машини з гідропневматичною підвіскою - Дущенко, Владислав Васильович; Нанівський, Роман Антонович; Воронцов, Сергій Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Розглянуто загальну математичну модель руху колісної бойової броньованої машини по нерівностях, що дозволяє проводити дослідження з підвищення їх тактико-технічних характеристик. Складено систему диференційних рівнянь коливань підресореного корпусу, яка враховує коливання непідресорених мас, пробої підвіски, відриви коліс від нерівностей та можливість удару підресореним корпусом об міжколійний простір. Визначено силові фактори, що діють на підресорений корпус колісної бойової броньованої машини з боку гідропневматичної підвіски, яка має запропоновану кінематичну схему. Розроблено методику розрахунку удару підресореним корпусом об міжколійний простір. Отримані результати дозволяють проводити дослідження з підвищення тактико-технічних характеристик даних машин та оцінку і зниження навантажень на бронекорпус при русі по нерівностях, шляхом оптимізації характеристик системи підресорювання, що є особливо важливим для легкоброньованих машин.

A general mathematical model of the movement of a wheeled armored combat vehicle over unevenness is considered, which allows conducting re search on improving their tactical and technical characteristics. The calculation scheme of the oscillating system "sprung body-suspension-unsprung masses-profile of road irregularities" was developed. A system of differential equations of vibrations of the sprung body has been compiled, which takes into account the fluctuations of unsprung masses, suspension breakdowns, separation of the wheels from bumps and the possibility of the sprung body hitting the intertrack space. With the use of previously developed methods for calculating the kinematics and dynamic load of the hydropneumatic suspension and its proposed kinematic scheme, dependencies were obtained for calculating the force factors that act on the sprung body from the side of the suspension nodes and when it hits the intertrack space. With the help of experimental dependencies obtained for military tracked vehicles when their front (guiding or leading) wheel hits the ground, a methodology for calculating the impact of a sprung body on the intertrack space has been developed. The obtained results make it possible to carry out research on improving the tactical and technical characteristics of these machines and to evaluate and reduce the loads on the armored hull when moving over bumps, by optimizing the characteristics of the suspension system, which is especially important for lightly armored vehicles.
Determination of force factors acting on a spring wheeled machine body with hydro-pneumatic suspension
Keywords: колісна машина; гідропневматична підвіска; підресорений корпус; силові фактори; wheeled vehicle; hydropneumatic suspension; sprung body; power factors